Chemical Modification in the Design of Immobilized Enzyme Biocatalysts: Drawbacks and Opportunities. Issue 3 (11th May 2016) - Rueda, Nazzoly; dos Santos, Jose C. S.; Ortiz, Claudia; Torres, Rodrigo; Barbosa, Oveimar; Rodrigues, Rafael C.; Berenguer‐Murcia, Ángel; Fernandez‐Lafuente, Roberto
Abstract: Chemical modification of enzymes and immobilization used to be considered as separate ways to improve enzyme properties. This review shows how the coupled use of both tools may greatly improve the final biocatalyst performance. Chemical modification of a previously immobilized enzyme is far simpler and easier to control than the modification of the free enzyme. Moreover, if protein modification is performed to improve its immobilization (enriching the enzyme in reactive groups), the final features of the immobilized enzyme may be greatly improved. Chemical modification may be directed to improve enzyme stability, but also to improve selectivity, specificity, activity, and even cell penetrability. Coupling of immobilization and chemical modification with site‐directed mutagenesis is a powerful instrument to obtain fully controlled modification. Some new ideas such as photoreceptive enzyme modifiers that change their physical properties under UV exposition are discussed. Abstract : Enzymes under control : Chemical modification of enzymes and immobilization used to be considered as separate ways to improve enzyme properties. This review shows how the coupled use of both tools may greatly improve the final biocatalyst performance.